Future teachers faced with writing. Results from an action-research project - Campos Bandrés, Iris Orosia (Revista Complutense de Educación, 2022)
In recent years, different research has been carried out on the habits, beliefs and attitudes of future teachers towards reading. Nevertheless, there are still few studies that adress these issues with respect to writing. With the aim of contributing in this regard, and with the purpose of bringing theory to practice in the training of future teachers,we developed an action-research project based on the principles of free text. The participants were 102 students of the Degree on Primary Education. The objectives were: to analyze their previous experiences and beliefs regarding non-academic writing and to explore the impact of the project on their ideology and motivation towards this habit. Participants' reflections before and after the experience were collected and key informant interviews were conducted. Results show a generalized conception of writing under a merely instrumental perspective, as well as the impat of the two main areas of literacy –family and school– in the ideology of future teachers regarding this skill. There is also evidence of the extensive existence of a negative self-concept of students regardin their competence in written expression. Moreover, the space of reflection offered by the project favors a positive (re)encounter with the act of writing. With the results in mind and knowning the resistance to change presented by teachers' beliefs regarding language education is known, it seems appropriate to incorporate in the training of this collective practices that favor a reflective (re)encounter with writing for pleasure, as other authors have proposed for when it comes to literary reading.
Keywords: action research; language didactics; teacher education; written expression